Multiple regression analysis of some bottom soil properties on the growth of benthos in nursery ponds - Habib, M Ashan Bin; Haque, Imdadul; Ali, M Mohsin (Indian Journal of Fisheries, 2011)
The benthos are most important organismsof natural water bodies which aredirectly or indirectly used as food and energyfor fishes and other organisms. Variousphysico-chemical properties of bottom soilhave combined effect on the growth of benthos.Variations in production of benthos indifferent ponds at different depths and in differentmonths may be due to differential fertilityand ecological conditions p-evailing inthose habitats. The work on depthwise.monthwise and pondwise variations of benthos,the combined effect of bottom soilproperties on the benthos, their interactionsand intrarelations based on statistical analyses,are very rare (Ahmed et al. 1987, Habibet al. 1987). To analyse some of these aspects,the present work was undertaken